2003
DOI: 10.1021/jm0204542
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of a Tertiary Alcohol Series of Phosphodiesterase-4 (PDE4) Inhibitors:  Structure−Activity Relationship Related to PDE4 Inhibition and Human Ether-a-go-go Related Gene Potassium Channel Binding Affinity

Abstract: A SAR study on the tertiary alcohol series of phosphodiesterase-4 (PDE4) inhibitors related to 1 is described. In addition to inhibitory potency against PDE4 and the lipopolysaccharide-induced production of TNFalpha in human whole blood, the binding affinity of these compounds for the human ether-a-go-go related gene (hERG) potassium channel (an in vitro measure for the potential to cause QTc prolongation) was assessed. Four key structural moieties in the molecule were studied, and the impact of the resulting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
48
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 39 publications
0
48
0
Order By: Relevance
“…For example, compounds 21 and 23, as the pure Z-isomers, afforded the expected product with only a slight decrease in yields (entries 12 and 13) using our standard procedure, while compound 25 provided an excellent yield of 26 (entry 14). Introducing a bulky t-Bu group (27) into the alkynone provided a quantitative yield of the desired isoxazole 28 (entry 15). Compounds 29 and 31 introduce steric bulk at the ortho positions of the parent phenyl rings.…”
Section: (2)mentioning
confidence: 99%
“…For example, compounds 21 and 23, as the pure Z-isomers, afforded the expected product with only a slight decrease in yields (entries 12 and 13) using our standard procedure, while compound 25 provided an excellent yield of 26 (entry 14). Introducing a bulky t-Bu group (27) into the alkynone provided a quantitative yield of the desired isoxazole 28 (entry 15). Compounds 29 and 31 introduce steric bulk at the ortho positions of the parent phenyl rings.…”
Section: (2)mentioning
confidence: 99%
“…It binds away from the bimetallic ion center, thus rendering its insensitivity towards Mg 2+ ion with a K d of 4700 nM with the apoenzyme [28]. Over the years, several thousands of catechol-ether based PDE4 inhibitors have been synthesized including the prototypical rolipram, and the more advanced second generation compounds such as roflumilast, cilomilast and L-869,298 [29]. Studies of over 30 of their published PDE4 cocrystals revealed that they all rely on a hydrogen bonding interaction between the invariant glutamine and their common catechol-ether oxygens, and a hydrogen bond Fig.…”
Section: Two-point Anchoring Model For Most Catechol-ether Based Inhimentioning
confidence: 99%
“…11 Candidate 3 was identified as a potent, selective PDE-IV inhibitor 12 and a 14 C-labeled tracer was needed for drug metabolism studies. Thanks to the effort of Merck process research, a 13-step synthesis of 3 was developed, and the compound 4 is an advanced intermediate from the 9th step of that very …”
Section: Introductionmentioning
confidence: 99%